(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to identify ((the effect of teaching the similarities strategy on the achievement of the students of the second intermediate grade in biology)).In order to achieve the aim of the research, the following zero hypothesis was formulated: ((There is no statistically significant difference at the level of significance (0.05) between the mean scores of the students of the experimental group who study according to the strategy of similarities and the average scores of the students of the control group who study according to the usual method in Achievement test in biology).